Matter Instability in Theories with Modified Induced Gravity - Kourosh Nozari; Faeze Kiani (Advances in High Energy Physics)
Matter stability is a necessary condition to have a cosmologically viable model. Modified gravity in the spirit of f(R) theories suffers from matter instability in some subdomains of the model parameter space. It has been shown recently that the late-time cosmic speedup can be explained through an f(R)-modified induced gravity program. In this paper, we study the issue of matter instability in a braneworld setup with modified induced gravity.